The Silent War in the Indian Ocean: Who Controls Asia’s Sea Lanes? - Bukhari, Syed Rizwan Haider; Khan, Haider Ali (ACADEMIA International Journal for Social Sciences, 2025)
The Indian Ocean is expected to become a key strategic platform in determining trading patterns in the world, energy security, and the current state of power balance in Asia. This paper will discuss the novice Silent war in the area where the key players, especially India, China, and the United States of America, are struggling to gain dominance over the key sea routes and nautical bottlenecks connecting Asia to the world markets. The discussion examines, the three aspects of the geopolitical, the economic and the military aspects of maritime competition by examining issues of navalization, the development of port infrastructure and new strategic alliances. Based on qualitative research and use of case studies of major chokepoints such as Strait of Hormuz and Strait of Malacca, the study evaluates the impact of who has control in strategic autonomy and regional stability through control of maritime routes. Based on the findings, modern leadership in the Indian Ocean is getting more technologically integrated, networked, and infrastructure-linked than the traditional fleet-based form of warfare and it has critical ramifications on the future strategy of Asia.